Assessing perceptions of establishing a vaccine pooled procurement mechanism for the Western Pacific Region. - Alice Abou-Nader; James D Heffelfinger; Ananda Amarasinghe; E Anthony S Nelson (PLOS Global Public Health)
This study explored the demand and interest among countries in the World Health Organization Western Pacific Region (WPR) to establish and participate in a regional vaccine pooled procurement mechanism. National counterparts affiliated with Ministries of Health that are involved in the national procurement of vaccines within the WPR were identified and invited to complete surveys. Out of 80 counterparts invited, 17 (21%) responded, representing 13 of the 27 WPR countries. Five countries expressed interest in participating in a regional pooled procurement mechanism, 3 expressed lack of interest and 5 did not respond to the question. Preferred characteristics of the procurement mechanism, included flexible participation (i.e. non-compulsory), payment in local currency before receipt of goods and a fixed price for vaccines (i.e. not tiered pricing). Vaccine pricing disparities were noted among upper middle-income and high-income countries for five of the 13 routine vaccines surveyed. Eight countries listed budget planning, quality of vaccines, timely delivery, cost-saving and payment after receipt as potential benefits of pooled procurement.